2018
DOI: 10.32737/2221-8688-2018-1-105-113
|View full text |Cite
|
Sign up to set email alerts
|

Research İnto Complex Formation of Tungsten(vi) With 2-Hydroxy-5-Bromothiophenol and Aminophenols

Abstract: Спектрофотометрическими методами изучена реакция комплексообразования вольфрама с 2-гидрокси-5-бромтиофенолом в присутствии аминофенолов. Из аминофенолов использованы 2-(N,N-диметиламинометил)-4-метилфенол, 2-(N, N-диметиламинометил)-4хлорфенол, 2-(N, N-диметиламинометил)-4-бромфенол. Найдены оптимальные условия образования и экстракции разнолигандных соединений и установлены соотношения компонентов в комплексах. Было установлено, что разнолигандные комплексы образуются в слабокислой среде (рН опт =3.4-4.8). М… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The molar absorbances ε are in the range of (2.7 -3.9)× 104. They are higher than those reported in [4,5,8,9,13,16]. Table 1 shows that the complexes with AP1 and AP2 involved have the best characteristics.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The molar absorbances ε are in the range of (2.7 -3.9)× 104. They are higher than those reported in [4,5,8,9,13,16]. Table 1 shows that the complexes with AP1 and AP2 involved have the best characteristics.…”
Section: Resultsmentioning
confidence: 64%
“…Methods for determining tungsten based on color reactions with organic reagents are numerous, but only some of them are used in analytical practice [1][2][3]. 2-hydroxy-5chlorothiophenol [4,5], nitro catechol [6,7], 2,3-dihydroxynaphthalene [7] as well as various ion-binding reagents [8][9] are used for the determination of tungsten. It is known that the hydroxythiophenolate complexes of tungsten are not soluble in chloroform whereas the mixed ligand complexes with hydrophobic amines and aminophenols are well dissolved in various organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Working solution with concentration of 0,1 mg/ml was prepared by dilution of stock with deionized water. HITP was synthesized according to the method [8]. The purity was checked by paper chromatography and melting temperature determination.…”
Section: Reagentsmentioning
confidence: 99%
“…Chromium oxidation studies. It is known that hydroxyhalogenthiophenol has reducing properties in an acidic environment [6,8]. Previous studies with Cr(VI)-H 2 L-HAm and Cr(III)-H 2 L-HAm showed that only Cr(III) forms stable complexes with this reagent.…”
Section: Reagentsmentioning
confidence: 99%
“…Spectrophotometric methods [1][2][3][4][5] are among the most precise instrumental methods of analysis for the determination of elements in trace amounts. These methods are remarkable for their versatility, sensitivity and precision.…”
Section: Introductionmentioning
confidence: 99%